MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Sulistyowati, Tri Sulistyowati (Dharmas Education Journal (DE_Journal), 2023)
The background of this research is the lack of creative thinking skills of students in grade VI of SDN Plangkrongan. To solve these problems using the Project Based Learning (PjBL) learning model. In this study using classroom action research with two separate cycles, and in it there are processes of planning, implementation, analysis and reflection. The research subjects in class VI were 20 students at SDN Plangkrongan. The results of this study indicate that the Project Based Learning learning model can improve students' creative thinking skills. Based on pre-cycle data, students are in the category of high creative thinking 15%, 25% sufficient and 60% low. In cycle I, those in the category of high creative thinking were 65%, 35% sufficient, and 20% low. In cycle II, students who were in the category of high creative thinking were 80%, 20% sufficient and 0% low. This shows that students' abilities have increased in each cycle through project based learning (PjBL).